PENGARUH MODEL CONTEXSTUAL LEARNING PADA HASIL BELAJAR SISWA MATA PELAJARAN IPA - Barotut taqiyah, Baeti (JIPD (Jurnal Inovasi Pendidikan Dasar), 2023)
This article is motivated by the low student learning outcomes in learning science in elementary schools. The author reviews the results of previous studies to analyze their success systematically. the criterion of the selected journal is regarding the influence of the contextual learning model on student learning outcomes in elementary schools. The importance of choosing the right learning model affects the level of children's interest, and one of the factors for the low learning outcomes of children is due to a lack of interest. Using this contextual learning model will help achieve the effectiveness of the learning process, direct students to be more comfortable in the learning process, make students feel more meaningful learning because it is combined with real events and provides direct experience to students. This contextual learning model will greatly assist teachers in improving the learning outcomes of elementary school students, especially in science material. This study aims to determine the effect of the contextual learning model on the learning outcomes of elementary school students in science subjects. This type of research uses literature study research.